RELATED SUBSTANCE METHOD DEVELOPMENT AND VALIDATION OF LOXAPINE SUCCINATE IN CAPSULE DOSAGE FORM BY REVERSE PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - KHUSHBU A THAKOR; PASHA TY (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study gives a simple, rapid, and accurate stability indicating reverse phase high-performance liquid chromatography method for the determination of loxapine succinate and its related substance (related compound A) in capsule dosage form. Methods: Loxapine succinate and its related substance were attained on a C18 Purospher star (250 mm × 4.6 mm, 5 μm particle size) column at 254 nm detection wavelength, 1.0 ml/min as a flow rate, and 10 μl injection volume. Water:methanol: Triethylamine: Tetrahydrofuran (50:40:1:10) was used a mobile phase, and column oven temperature was 30°C. Results: The resolution between loxapine succinate and known unknown impurities was >2.0. The correlation coefficient (0.999) value indicates the linear relationship between the concentration and peak areas. The accuracy study was performed by spiking method. Loxapine succinate was exposed to the stress condition of hydrolysis (acid and base), oxidative, thermal, and photolytic degradation. Loxapine succinate was found to degrade unquestionably in acid and base stress condition and almost stable in oxidative, thermal, and photolytic conditions. Conclusion: The degradant products were well resolved from leading peak and its related compound A peak and any other unknown peak justifying the stability indicating capability of the method. The developed method was validated as per the ICH guidelines. This method is used for periodic analysis in laboratory.